Factors Influencing Satisfaction With Pharmacy Services In Out Patients At DKT Madiun Hospital - Hanik Mariana Dewi; Ririn Ernawati; Fidi Setyawan (Universitas STRADA Indonesia, 2023)
Patient satisfaction is one of the components used to assess whether a service system is good or bad. The aim of this research is to determine the factors of attitude and waiting time with satisfaction with pharmaceutical services. This type of research is correlation analytic with a cross-sectional approach. The sampling technique was purposive sampling with a sample of 216 patients. Data collection uses questionnaires (attitude and satisfaction) and watches (waiting time). The research results showed that the average waiting time was around 17.49 minutes, as many as 117 (81.9%) respondents from pharmacy staff behaved well and 185 respondents (85.65%) were satisfied with pharmacy services. The Spearman rank statistical test shows that there is a relationship between the officer's attitude and waiting time and satisfaction with pharmaceutical services (p value 0.04 and 0.000 < α = 0.05). Attitudes and waiting times for pharmaceutical services are important factors in improving the quality of pharmaceutical services.